Aerodynamic Shape Optimization of Wing–Fuselage Intersection for Minimum Interference Drag - Nuno M. B. Matos; André C. Marta (Aerospace)
Interference drag in wing–fuselage intersection regions is a complex aerodynamic phenomenon where secondary flows and separation conditions might occur if not properly addressed in the aircraft design. In this work, the optimal shape of the intersection region between the wing and fuselage of a MALE UAV is studied using gradient-based optimization and free-form deformation techniques. High-fidelity fluid computational dynamics solving the RANS equations are employed, together with the corresponding adjoint formulation to compute the gradients of the aerodynamic metrics. Different shape deformation techniques are explored for both the fuselage and wing, and several combinations of design variables are studied. Fuselage shape deformations were found to be more efficient in the removal of the secondary flow near the wing root trailing edge. Reducing the cross-sectional area of the fuselage near the wing leading edge and increasing it near the trailing edge was shown to reduce drag, demonstrating that secondary flow mitigation is more relevant than reduced frontal area. A <semantics>2%</semantics> total drag reduction was obtained by simultaneously shaping both the fuselage and the wing in the intersection region. The optimized wing–fuselage interface remained sharp, without fairings, due to the limitation of the deformation technique to modify the original topology.